A comparative Study of Some Nutritional Aspects of Camel and Cattle Meats and the Effect of Chilling and Freezing Storage on the Meat Lipid Peroxidation - Abd-Allah, Sherief Mohammed Sayed; Ahmed Ismail, Hesham Abdel-Moez; Abdel-Rasoul, Mohammed Abdel-Salam Ahmed (International Journal For Research In Agricultural And Food Science, 2019)
The present work aimed to study and compare some nutritional aspects of cattle and camel meats of both young and old ages, and the lipid peroxidation behavior during chilling and freezing storage of such meats. A total of 36 fresh meat samples (10 of each of young and old cattle, 9 of young and 7 of old camel) were randomly collected from butcher shops at the same day of slaughter. The pH and the proximate composition"%" (moisture, protein, fat, ash) were estimated. Carbohydrate (%) and gross energy content (Kcal/100g) were calculated. The TBA value (mg malonaldehyde/kg flesh) changes during chilling (4ºC) and freezing (-10ºC) storage was assessed. For fresh samples of young camel meat, the moisture, protein, fat, ash, carbohydrates and energy mean values were 76.36 ± 0.34, 20.13 ± 0.29, 1.89 ± 0.16, 1.06 ± 0.03, 0.56 ± 0.08, and 99.78 ± 2.01, while for young beef samples were 73.79± 0.47, 21.29 ± 0.35, 3.22 ± 0.26, 1.08 ± 0.04, 0.61 ± 0.09 and 116.61 ± 2.69, respectively. For fresh samples of old camel meat, the mean values were 76.35 ± 0.33, 20.36 ± 0.26, 1.64 ± 0.08, 1.05 ± 0.03, 0.60 ± 0.09, and 98.57 ± 0.33; and for old beef samples were 76.11 ± 0.57, 19.57 ± 0.48, 2.54 ± 0.26, 1.32 ± 0.11, 0.46 ± 0.07 and 102.96 ± 3.33, respectively. Protein content was comparable in both cattle and camel meats, while fat was significantly (p<0.05) lower in camel meat. Freezing storage results in significant (P<0.05) decrease in moisture, while protein and energy were significantly (p<0.05) increased, and other items were changed insignificantly (P>0.05). The pH values showed significant (P<0.05) increase for old ages samples but non-significant (P>0.05) for young ages during chilling storage. The TBA values showed steady increase in all samples during chilling and freezing storage, the rate of increase was lower in camel meat than in beef. In conclusion, camel meat ranked superior to that of cattle of nearly similar age "had significantly lower fat content and keep longer at chilling and freezing".